Challenges of Accessibility to Information Resources by Prison Inmates - Emasealu, Helen Uzoezi (International Journal of Knowledge Content Development & Technology, 2018)
Prisons are mostly filled with social deviants and like other correctional institutions, deserve organized information (provision) centers such as library. A study on library information needs and accessibility by prison inmates was conducted at Kuje prison, Abuja and Kaduna prison, Kaduna, Nigeria, both of which have functional libraries. A sample of 898 inmates was randomly selected from all the convicted inmates in the two prisons. A total of 106 inmates were selected from Kuje prison and 792 from Kaduna prison. A well-structured questionnaire was used to collect data from the inmates. All the 898 inmates responded. A total of 786 (87.9%) males and 112 (12.4%) females were involved in the study. With regards to the educational level attained by the inmates, 347 (38.6%) had Junior Secondary School Certificate while 323 (30.0%) had Senior School Certificate both accounting for 74.6% of the sampled population. In areas of information needs, 94.5%, 96.1%, 98.7%, 99.4%, 100%, and 100% of the respondents indicated that information on current affairs, survival and coping, educational support, legal aid, skill acquisition, and health, respectively were highly needed by the inmates. Out of the 12 information resources listed, only newspaper, novel, handbook and manual, and bulletin were readily accessible with percentage accessibility of 60.7, 7.8, 6.8, and 1.9, respectively. One major reason adduced by the respondents for limited access to information resources was the very strict rules and regulations in the prison. Providing more library resources and granting the inmates more access to the library would assist in character reformation and rehabilitation of the inmates. URL: http://ijkcdt.net/xml/14412/14412.pdf